An assessment of three little-noticed papers on avian nomenclature by G. N. Kashin during 1978–1982 - Gregory, Steven M. S.; Dickinson, Edward C. (Zootaxa, 2012)
Overlooked and unanswered nomenclatural observations from 30 years ago, mostly based on perceived shortcomings in theCheck-list of Birds of the World by J. L. Peters and his successors, are examined. Many are rebutted, a number endorsed and recommended.